An Analysis of Translation Problems Faced by the Third Year English Department Students of UNP in Translating Historical Recount Text - Astria Syonia; Rusdi Noor Rosa (Universitas Negeri Padang, 2020)
A translator should be able to convey the intended meaning contained in the source language into the target language. The result of initial observation is some of the students in translation class tend to translate without reading the whole text that might lead to misunderstanding of source text. There might be some other translation problems faced by the student translators. This study aims at analyzing the problems faced by the student translators in translating a historical recount text from English into bahasa Indonesia. This study used a descriptive method. The participants were the third year English Department Students who took translation as their elective course. The data were collected using Keylogging (Translog) tools for more representative data. The data were analyzed using a translation process procedure. The results indicate that there are ten problems founds in the students’ translation, they are the improper use of generalization technique, improper of borrowing technique, target language structure, meaning deletion, the improper use of literal technique, context misunderstanding, target language interference, meaning addition, inability to find right equivalent, source text misunderstanding. These problems are mainly caused by the students’ low translation skills.